PENGARUH PENCUCIAN PADA TANAH TERCEMAR NATRIUM TERHADAP PERTUMBUHAN TANAMAN - Adji, Sandra Sukmaning (LPPM Universitas Terbuka, 2008)
Sodium (Na) was found as one of chemical elements that able to disturb plants that grow along the Cikijing river. This river water that had been detected as contains high sodium, whereas the river water is still used by local farmers to irrigate their rice fields. The aim of this research are to identify the effect of bleaching process on the Na polluted soils toward the plant growth. Experiment was conducted in a greenhouse using rice field soils that contains high Na as the experiment material. The soils were washed using deepwater well and filtered water. Filtering was processed using zeolit and white sand, whereas rice plants were used as indicator. Result show that bleaching with deep water well and filtered water are both able to reduce the contain on Na in the soils. The application of deep well water and filtered water has shown a significant influence toward the height of the rice plants and the number of productive rice buds. The rice plants irrigated by deep water well are seen as higher in growth and bigger in number of productive rice buds compare to rice plants watered with filtered irrigation. The length (height) of plant watered with deep water well (99.1 cm) was significantly different with rice plants watered with filtered water (80.8 cm). On the other hand, the average number of 36 productive rice buds watered with deep water well is significantly different with rice plants watered by filtered water in the number of 23.